Advance relief in aircraft finance and the Cape Town Convention - Traschler, T (2015)
The Cape Town Convention came into force on the 1st April 2004 and the Aircraft Protocol came into force on 1st March 2006. To date, the Convention has sixty-six States Parties, the Aircraft Protocol fifty-eight States Parties, and together they can be regarded as one of the most successful recent commercial law treaties. The Convention's overriding object is to offer creditors the highest possible protection in the form of an effective, speedy and strong legal remedial framework for the international enforcement of creditors rights in the event of the debtor's default or insolvency. The underlying rationale is that this will lead to significant reductions in borrowings costs for lenders to the advantage of all interested stakeholders in the aircraft sector. However, without effective implementation of the remedial system of the Convention and the Aircraft Protocol, it is difficult for financiers to have confidence that they are able to defend their legal rights effectively. First, this thesis examines the legal nature and purpose of Article 13 ("Relief Pending Final Determination") of the Cape Town Convention, since it does not fit any traditional remedy under domestic law. Secondly, this thesis answers the crucial questions whether, and to what extent, elements of national procedural law in a Contracting State are relevant to the application of advance relief under the Convention. Further, to the extent that domestic procedural law may be applicable, the thesis examines if the relevant domestic rules of procedure are in conformity with the fundamental principles of the Cape Town Convention and the legal nature of advance relief. Ultimately, it thereby clarifies the relationship between the Convention and national procedural law in the context of Article 13.